(untitled) (Jurnal Mekanikal, 2018)
A computational method has been developed to realize an efficient and accurate user friendly computational program called RocketCalculator, which integrates carefully assessed methodologies and offer flexibilities of the rocket configurations and velocities up to Mach number 3.0 and angle of attack of 25 degrees. The RocketCalculator is capable of analyzing the configurations of wing-alone, bodyalone, wing-body combination, and wing-body-tail combination of rocket. USAF Datcom Method has been chosen as the analysis method and the programming language is Microsoft Visual Basic. The result would be displayed in form of the corresponding lift (CL ), normal force (CN ) and drag (CD ) coefficients at certain Mach number and angle of attack. Experimented data for several models have been taken out from available sources to validate the program output. Comparisons of the program output and experimental results generally show good agreement with average error of less than 10%.